2003
DOI: 10.1029/2003gl017139
|View full text |Cite
|
Sign up to set email alerts
|

Properties of high heliolatitude solar energetic particle events and constraints on models of acceleration and propagation

Abstract: [1] We analyse 9 large solar energetic particle (SEP) events detected by the Ulysses spacecraft at high heliolatitudes during the recent solar maximum polar passes. Properties of time intensity profiles from the Ulysses/COSPIN instrument are compared with those measured by SOHO/COSTEP and Wind/3DP near Earth. We find that onset times and times to maximum at high latitude are delayed compared to in-ecliptic values. We show that the parameter which best orders these characteristics of time profiles is the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 10 publications
5
43
0
Order By: Relevance
“…Dalla et al (2003a, b) studied the differences between SEP onset times and times-to-maximum as a function of latitude and found that the delays at Ulysses were best organized by the difference in latitude between the associated flare and the s/c. Dalla et al (2003b) concluded that the presence of a shock is not necessary for creating the near-equal intensities observed at Ulysses and near Earth during decay phases; these observations are better explained by diffusion across the main IMF. Figure 53 shows intensity-time profiles of ∼1-200 MeV protons and ∼3-8 MeV electrons during the January 1, 1978 SEP event as observed at four different s/c.…”
Section: Sep Observations At Helios and Ulyssesmentioning
confidence: 88%
“…Dalla et al (2003a, b) studied the differences between SEP onset times and times-to-maximum as a function of latitude and found that the delays at Ulysses were best organized by the difference in latitude between the associated flare and the s/c. Dalla et al (2003b) concluded that the presence of a shock is not necessary for creating the near-equal intensities observed at Ulysses and near Earth during decay phases; these observations are better explained by diffusion across the main IMF. Figure 53 shows intensity-time profiles of ∼1-200 MeV protons and ∼3-8 MeV electrons during the January 1, 1978 SEP event as observed at four different s/c.…”
Section: Sep Observations At Helios and Ulyssesmentioning
confidence: 88%
“…In Figure 2 we show summary plots of the events number 2, 3 and 4 of Sanderson et al (2003b). These events have also been studied in detail by Dalla et al (2003aDalla et al ( , 2003b, Lario et al (2004) and McKibben at al. (2003).…”
Section: The Second Northern Polar Passmentioning
confidence: 85%
“…Larger than expected delays in onset times were observed for most of these highlatitude events (Dalla et al, 2003a, corresponding typically to 120 to 350 minutes from the flare onset. These delay times and the path lengths were correlated by Dalla et al (2003aDalla et al ( , 2003b) against several variables. The best correlation was found with difference in latitude between the flare site and the latitude of Ulysses, this correlation being surprisingly better than the correlation with the angular separation between the site and Ulysses.…”
mentioning
confidence: 99%
“…Whether or not an SEP event will be detected, for example near Earth, depends on the location at the Sun of the parent event: eruptions at Western locations on the solar disk have a much higher likelihood of resulting in an SEP event at Earth, due to the curvature of the Parker spiral interplanetary magnetic field. However, in many events particles can be detected at locations widely separated, either in longitude (e.g., [124]) or in latitude (e.g., [25]), from the parent region. While this was thought initially to apply only to gradual events, it has been shown that impulsive events can also be detected over wide longitudinal ranges [147].…”
Section: Location Of Parent Active Regionmentioning
confidence: 99%